2018
DOI: 10.1002/lary.27068
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal cancer: Global socioeconomic trends in disease burden and smoking habits

Abstract: 4. Laryngoscope, 128:2039-2053, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…A paucity of treatments and an age shift down in high risk behaviors including alcohol and tobacco use, and the sexual comportments of young people, have likely contributed to this alarming trend [2,3,4,5]. The burden of squamous cell carcinomas of the head, neck, oral cavity and nasopharynx, and larynx is much higher in less developed countries where variations of smokeless tobacco and the chewing of betel and areca nuts are cultural norms, and outcomes are much worse [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A paucity of treatments and an age shift down in high risk behaviors including alcohol and tobacco use, and the sexual comportments of young people, have likely contributed to this alarming trend [2,3,4,5]. The burden of squamous cell carcinomas of the head, neck, oral cavity and nasopharynx, and larynx is much higher in less developed countries where variations of smokeless tobacco and the chewing of betel and areca nuts are cultural norms, and outcomes are much worse [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, a study showed that most of LC included in the global burden was found in high socioeconomic countries before 2010 and now has shifted toward low socioeconomic countries. 4…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cigarette smoking is strongly associated with an increased risk of LSCC in a dose-response and time-response manner [58]. Although significant smoking trend reductions have led to the declined global burden of LSCC in developed countries, smoking continues to trend upward in low socioeconomic countries, potentially inducing an increased burden of LSCC in the future [59]. Notably, smoking prevention programs conducted in health care settings and interventions, including enhancement of interpersonal communication and support strategies, can be effective in preventing smoking behavior for three months to four years in children and adolescents [60].…”
Section: Discussionmentioning
confidence: 99%